On Using Artificial Intelligence in the Search of the Best Professional Resumes - Charcon, Douglas; Omar, Nizam; Monteiro, Luiz Henrique Alves (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2022)
Digital transformation has changed how companies develop, manufacture and deliver their products and services. The search for competitiveness and greater market share have been driven companies to use automation and digital technologies to become more attractive and continue to deliver value to their customers. However, the human factor remains decisive for the company´s success. In this context, the Human Resources (HR) team has the role of strategically improving the company composition. In this paper, we present the development of an application, based on Artificial Intelligence and Digital Data Processing tools, with the aim of helping HR teams to seek talents and, thereby, to contribute to the business success. This application was tested and validated by using real-world databases of professional resumes.